Why English exhibits determiner-possessor complementarity and Slovene doesn't - Lipovšek, Frančiška (ELOPE (Ljubljana), 2004)
The aim of the paper is to provide an explanation for the following diff erence between English and Slovene: whereas in English a definite determiner and a possessor are in complementary distribution, in Slovene the two categories are perfectly compatible. Arguing that the traditional approach to determiner-possessor complementarity is inadequate, the paper proposes an explanation that has been developed within the framework of generative grammar: languages exhibiting determiner-possessor complementarity are characterized by the presence of the ! def feature on the functional head Pos. The generative approach also shows that (with the definite article and a demonstrative occupying different structural positions) determiner-possessor complementarity is in fact twofold, comprising (i) article-possessor complementarity and (ii) demonstrative-possessor complementarity.
Keywords: angleščina; členek (ling.); določni člen; generativna slovnica; kazalni zaimek; kontrastivna lingvistika; slovenščina